Navigating the Digital Frontier: A Literature Review on Business Digitalization - Benga, Btissam; Elhamma, Azzouz (European Scientific Journal, ESJ, 2024)
The rise of digital technology has compelled organizations to undergo significant changes or, at the very least, reassess their operational strategies. Many major corporations have poured significant financial resources into what is commonly referred to as "Digitalization." Digitalization, the integration of digital technologies into various aspects of life and business, has revolutionized industries across the globe, but even if Digitalization offers numerous benefits, including increased efficiency, innovation, and improved customer experiences, it also presents challenges such as security risks, the digital divide, technological dependency, and ethical considerations. The objective of our article is to present a literature review on digitalization and provide an overview of the notable constraints and obstacles associated with digitalization and its advancement. The literature review concerning digitalization was conducted through a systematic search across various research databases and platforms including but not limited to ScienceDirect, Google Scholar, and ACM Digital Library. Articles, research papers, books, and conference proceedings published between 2012 and 2024 were considered for inclusion in the review. Synthesizing and analyzing information from various publications and authors revealed a comprehensive understanding of the challenges and opportunities associated with digitalization. The results highlighted common themes such as security risks, the digital divide, technological dependency, ethical considerations, and the demand for digital resources. Additionally, the review identified key strategies for addressing these challenges and leveraging digital technologies for positive societal impact.